Redefining Religious Moderation Education for Urban Muslim Youth - Jati, Wasisto; Bachtiar, Hasnan (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
Religious moderation has been a government policy since 2015, aimed at countering radicalism and extremism. However, the hierarchical implementation of the program has led to the labeling of "moderate" and "conservative", and the policy's understanding remains unclear among the community, especially the middle class and youth. Despite the government's campaign, intolerance persists. This research aims to review the religious moderation policy and explore how urban Muslim youths could contribute to religious moderation education. The method involves in-depth interviews with urban Muslim youths in Manado and Semarang and critical analysis of relevant documents. The findings suggest that urban Muslim youths prioritize religious moderation through intensive dialogue and gatherings. Current educational practices should incorporate these informal approaches to be more effective. The inclusion of urban Muslim youths in religious moderation education appears to be a promising way to encourage religious moderation in Indonesia. This highlights the need for religious moderation implementation to be responsive to public aspirations.